Growth and Production of Lemon Basil (Ocimum basilicum L.) Grown in Different Compositions of Urea Fertilizer and Cattle Urine - Aranta, Dwi Pradana; rahayu, arifah; mulyaningsih, yanyan (JURNAL AGRONIDA, 2019)
This study was aimed at assessing the effects of different rates of cattle urine and urea fertilizer and on the growth and production of three lemon basil accessions. A factorial completely randomized design with two factors was used. The first factor was the composition of cattle urine and urea fertilizer consisting of six levels, namely 100% cattle urine, 75% cattle urine + 25% urea, 50% cattle urine + 50% urea, 25% cattle urine + 75% urea, 100% urea, and 0% cattle urine + 0% urea. The second factor was lemon basil accession consisting of three levels, namely Bogor, Cianjur, and Sukabumi accessions. Results showed that Sukabumi acession had the highest number of leaves, leaf area, branch length, number of branches, branch diameter, fresh weight and dry weight. Urea and urine cattle compositions did not give significant effects on parameters measured. However, compared to no fertilizer tretament, other treatments gave significant differences in parameters measured. It was concluded that cattle urine could be used to substitute urea fertilizer.